Pengembangan Pembelajaran Lari Gawang melalui Modifikasi Alat Athletic Kids di SDN 1 Plosorejo - Lubna Lauziah, Qudduussiyatul; Andi Susilo, Eko (utile: Jurnal Kependidikan, 2026)
Success in physical education learning is closely related to adequate facilities and infrastructure. Without these resources, learning cannot be optimally conducted. Modification of children's athletic equipment, especially for hurdle running learning, needs to be carried out with the development of a new hurdle media that can be modified in height according to the students' abilities. This research includes development with a sample of 93 students from 1st to 3rd grade in elementary school. The results of this product development received an overall score of 89%, qualifying as very good/eligible for development, according to the total respondents of each class, who scored 82% from 1st-grade students, 97% from 2nd-grade students, and 90% from 3rd-grade students.